Co-encapsulamento de Lactiplantibacillus plantarum associado aos compostos fenólicos extraídos da folha de bambu (Dendrocalamus asper) - Torres, Stéphanie Pereira (2024)
Bioactive compounds extracted from alternative sources such as bamboo leaves, in addition to beneficially and phytochemically enriching the microcapsules, protect the probiotic cells of Lactiplantibacillus plantarum. The microcapsules produced by spray drying at concentrations ME-0%, ME-5%, ME-10% and ME20% protected and controlled the release of probiotic cells in the gastrointestinal simulation at a concentration of 20%, maintaining stable viability in the ileum. In addition, the encapsulation method provides probiotic protection subjected to different heat treatments, thus L. plantarum showed excellent resistance to 72°C for 15s containing 20% extract, with a viable count of 7.1 log CFU/g. Furthermore, the addition of bamboo leaf extract to the microcapsules containing L. plantarum improved the stability of the probiotic and it was possible to achieve excellent stable viability at colder temperatures, compared to room temperature. Thus, the application of bamboo leaf extract is a possible promising alternative in the protection of probiotics such as microencapsulated L. plantarum, since in addition to protecting against high temperatures in a short period, and against low temperatures for 9 weeks, it contributed phytochemically by providing microcapsules rich in bioactive compounds.